Post-traumatic Stress among adolescents surviving Nepalese earthquake and children of immigrants in Finland - Silwal, Sanju (fi=Turun yliopisto|en=University of Turku|, 2021)
The aim of this dissertation was to identify risk factors associated with posttraumatic stress symptoms (PTSS) using two study designs: a longitudinal postearthquake survey and a Finnish population-based study. Studies I and II were carried out 18 and 31 months after the 2015 Nepal earthquake. They examined the prevalence of psychiatric symptoms, namely PTSS and depressive symptoms among 893 adolescents aged 11-17 years, together with potential risk factors associated with their psychiatric symptoms. The participants were enrolled from schools (grades 7- 10) from two earthquake-affected areas, one more severely affected than the other. Psychiatric symptoms were assessed using the Child PTSD Symptom Scale and Depression Self-Rating Scale. The aim of Study III, the Finnish population-based study, was to examine the association between parental immigration status and posttraumatic stress disorder (PTSD) in their offspring. The study was a nested matched case-control study that used several nationwide registers. The cases were all singleton births in Finland between 1 January 1987 and 31 December 2010, who had been diagnosed with PTSD by the year 2012 in the Care Register for Health Care. The controls were all singletons born in Finland during the study period, alive and living in Finland when the matched cases were diagnosed. The study included 3639 cases and 14434 controls. In Study I, the prevalence of PTSS and depressive symptoms among adolescents was higher in the severely affected area. The factors associated with psychiatric symptoms were being female, pre-earthquake trauma exposure and being trapped and/or wounded. In Study II, no significant change in the prevalence of PTSS and depressive symptoms was observed from 18 months to 31 months after the earthquake. Living in the severely affected area and post-earthquake trauma exposure increased the risk for delayed and chronic PTSS and depressive symptoms. In Study III, children with an immigrant father had at an increased risk of developing PTSD, compared to those with two Finnish parents. The risk of PTSD increased if the child’s father migrated to Finland less than five years before their birth and the father was born in North Africa or the Middle East. These studies highlighted the need for psychosocial support and services for earthquake survivors and secondgeneration immigrants.

Traumaperäinen stressi nuoruusikäisillä maanjäristyksen jälkeen Nepalissa sekä maahanmuuttajien lapsilla Suomessa Väitöskirjan tavoitteena on tunnistaa traumaperäisen stressihäiriön (PTSD) oireiden riskitekijöitä hyödyntämällä kahta eri tutkimusasetelmaa: maanjäristyksen jälkeen toteutettua seurantatutkimusta sekä suomalaista väestötutkimusta. Tutkimuksessa selvitettiin psyykkisten oireiden (traumaperäiset oireet ja masennusoireet) esiintyvyyttä 839:lla 11–17-vuotiaalla nuorella 18 ja 31 kuukautta Nepalin vuoden 2015 maanjäristyksen jälkeen sekä tutkittiin psyykkisten oireiden mahdollisia riskitekijöitä. Osallistujat saatiin kouluista (luokka-asteet 7–10) kahdelta alueelta, joista toinen oli kärsinyt maanjäristyksestä enemmän. Psyykkisiä oireita kartoitettiin Child PTSD symptom scale –kyselyn ja Depression Self-Rating Scale –kyselyn avulla. Suomalaisessa rekisteritutkimuksessa tavoitteena oli tutkia vanhempien maahanmuuttajuuden ja heidän jälkeläisillään diagnosoidun traumaperäisen stressihäiriön välistä yhteyttä. Tutkimus on pesitetty, kaltaistettu tapaus- verrokkitutkimus, joka perustuu useisiin kansallisiin rekistereihin. Tapaukset kattoivat kaikki Suomessa yksösraskauksista ajalla 1.1.1987–31.12.2010 syntyneet lapset, jotka olivat Hoitoilmoitusrekisterin mukaan saaneet PTSD-diagnoosin vuoteen 2012 mennessä. Verrokit poimittiin samalla ajanjaksolla Suomessa yksösraskauksista syntyneistä henkilöistä, jotka olivat elossa ja asuivat Suomessa ajankohtana, jona kaltaistetut tapaukset diagnosoitiin. Tutkimuksessa oli 3639 tapausta ja 14 434 verrokkia. Tutkimuksessa I traumaperäisen stressihäiriön sekä masennuksen oireiden esiintyvyys nuorilla oli korkeampi maanjäristyksestä pahemmin kärsineellä alueella. Psyykkisiin oireisiin olivat yhteydessä naissukupuoli, altistuminen traumaattiselle kokemukselle ennen maanjäristystä sekä loukkuun jääminen tai loukkaantuminen. Tutkimuksessa II ei havaittu merkitsevää muutosta traumaperäisten oireiden tai masennusoireiden esiintyvyydessä 18 ja 31 kuukauden välillä maanjäristyksen jälkeen. Asuminen maanjäristyksestä pahoin kärsineellä alueella sekä maanjäristyksen jälkeinen trauma-altistus lisäsivät viivästyneiden ja kroonisten PTSD- ja masennusoireiden riskiä. Tutkimuksessa III PTSD:n riski oli kohonnut lapsilla, joiden isä on maahanmuuttaja verrattuna lapsiin, joiden molemmat vanhemmat ovat suomalaisia. Jälkeläisten PTSD-riski oli kohonnut jos isä oli muuttanut Suomeen alle viisi vuotta ennen heidän syntymäänsä ja jos isä oli syntynyt Pohjois-Afrikassa tai Lähi-idässä. Tutkimus korosti maanjäristyksen kokeneiden sekä toisen polven maahanmuuttajien psykososiaalisen tuen tarvetta.